Drivers of amphibian population dynamics and asynchrony at local and regional scales. Issue 6 (11th April 2020) - Cayuela, Hugo; Griffiths, Richard A.; Zakaria, Nurul; Arntzen, Jan W.; Priol, Pauline; Léna, Jean‐Paul; Besnard, Aurélien; Joly, Pierre
Abstract: Identifying the drivers of population fluctuations in spatially distinct populations remains a significant challenge for ecologists. Whereas regional climatic factors may generate population synchrony (i.e. the Moran effect), local factors including the level of density dependence may reduce the level of synchrony. Although divergences in the scaling of population synchrony and spatial environmental variation have been observed, the regulatory factors that underlie such mismatches are poorly understood. Few previous studies have investigated how density‐dependent processes and population‐specific responses to weather variation influence spatial synchrony at both local and regional scales. We addressed this issue in a pond‐breeding amphibian, the great crested newt Triturus cristatus . We used capture–recapture data collected through long‐term surveys in five T. cristatus populations in Western Europe. In all populations—and subpopulations within metapopulations—population size, annual survival and recruitment fluctuated over time. Likewise, there was considerable variation in these demographic rates between populations and within metapopulations. These fluctuations and variations appear to be context‐dependent and more related to site‐specific characteristics than local or regional climatic drivers. We found a low level of demographic synchrony at both local and regional levels. Weather has weak and spatially variable effects on survival, recruitment and population growth rate. In contrast, density dependence was a common phenomenon (at least for population growth) in almost all populations and subpopulations. Our findings support the idea that the Moran effect is low in species where the population dynamics more closely depends on local factors (e.g. population density and habitat characteristics) than on large‐scale environmental fluctuation (e.g. regional climatic variation). Such responses may have far‐reaching consequences for the long‐term viability of spatially structured populations and their ability to respond to large‐scale climatic anomalies. Abstract : Few previous studies have investigated how density‐dependent processes and population‐specific responses to weather variation influence spatial synchrony at both local and regional scales. This article tackles this critical issue.